A report of two cases of dedifferentiated endometrioid carcinoma: A newly described underrecognized tumor of poor prognosis - Anup K Boler; Sana Akhtar; Arghya Bandyopadhyay; Shreosee Roy (Wolters Kluwer Medknow Publications, 2020)
Dedifferentiated endometrioid carcinoma or dedifferentiated endometrioid adenocarcinoma (DEAC) is defined by the presence of undifferentiated carcinoma with endometrioid carcinoma. Undifferentiated component can be misinterpreted as solid component of high-grade endometrioid carcinoma or sarcomatous component of malignant mixed mullerian tumor. We present two cases of DEAC. Two postmenopausal women underwent hysterectomy for vaginal bleeding. Microscopically, sections from the endometrial tumors showed a biphasic growth consisting of an undifferentiated component and a glandular component with sharp transition between the two components. The undifferentiated component showed focal positivity for cytokeratin and vimentin, while glandular component was diffusely positive for cytokeratin and negative for vimentin expression.